MicroRNA‐122 regulates hypoxia‐inducible factor‐1 and vimentin in hepatocytes and correlates with fibrosis in diet‐induced steatohepatitis. (28th July 2014) - Csak, Timea; Bala, Shashi; Lippai, Dora; Satishchandran, Abishek; Catalano, Donna; Kodys, Karen; Szabo, Gyongyi
Abstract Background & Aims miR‐122 is the most abundant miRNA in the liver particularly in hepatocytes where it targets cholesterol metabolism. Steatosis, a key component of non‐alcoholic fatty liver disease, is regulated by hypoxia‐inducible factor‐1α (HIF‐1α). Here, we hypothesized that reduced miR‐122 has a pathogenic role in steatohepatitis. Methods miR‐122 and its target genes were evaluated in mouse livers and/or isolated hepatocytes after methionine–choline‐deficient (MCD) or methionine–choline‐supplemented (MCS) diet. Results Liver and hepatocyte miR‐122 expression was significantly decreased in steatohepatitis. A maximum reduction in miR‐122 occurred at the fibrosis stage (8 weeks of MCD diet). MAP3K3, a miR‐122 target gene, was induced at all stages of non‐alcoholic steatohepatitis (NASH; 3–8 weeks) only at the mRNA level. Increased NF‐κB activation was found in MCD diet‐fed mice and MAP3K3 regulated the NF‐κB DNA binding in naive hepatocytes. HIF‐1α mRNA and DNA binding and expression of the HIF‐1α target gene, profibrotic lysyl oxidase, was increased in advanced steatohepatitis (8 weeks). In addition, increase in vimentin and Sirius red staining (liver fibrosis) was found at 8 weeks of MCD diet. Using miR‐122 overexpression and inhibition approaches, we confirmed that HIF‐1α, vimentin and MAP3K3 are novel miR‐122 targets in hepatocytes. We report transcriptional repression of miR‐122 in NASH. Decreased liver miR‐122 was associated with elevated circulating miR‐122 in both exosome‐rich and protein‐rich serum fractions. Conclusions Our novel data suggest that decreased liver miR‐122 contributes to upregulation of modulators of tissue remodelling (HIF‐1α, vimentin and MAP3K3) and might play a role in NASH‐induced liver fibrosis.